2022
DOI: 10.3389/fimmu.2022.834247
|View full text |Cite
|
Sign up to set email alerts
|

New Druggable Targets for Rheumatoid Arthritis Based on Insights From Synovial Biology

Abstract: Rheumatoid arthritis (RA) is a multifactorial autoimmune disease characterized by chronic inflammation and destruction of multiple small joints which may lead to systemic complications. Altered immunity via pathogenic autoantibodies pre-date clinical symptom development by several years. Incompletely understood range of mechanisms trigger joint-homing, leading to clinically evident articular disease. Advances in therapeutic approaches and understanding pathogenesis have improved prognosis and likely remission.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 149 publications
(185 reference statements)
1
7
0
Order By: Relevance
“…Using liquid chromatography coupled with mass spectrometry, T cell epitopes have been identified directly from inflamed synovial tissue, then tested for immunogenicity using patient samples. In one study, it has been noted that a peptide from a protein of P. copri 27 kDa (Pc-p27) stimulated T and B lymphocytes in 40% of patients with rheumatoid arthritis, but not in the control group or in patients with other rheumatic diseases [8,144,145]. This peptide is also presented by an HLA-DR receptor, which is consistent with existing data on HLA-DR and its relationship to the phenomenon of molecular mimicry.…”
Section: Molecular Mimicrysupporting
confidence: 75%
“…Using liquid chromatography coupled with mass spectrometry, T cell epitopes have been identified directly from inflamed synovial tissue, then tested for immunogenicity using patient samples. In one study, it has been noted that a peptide from a protein of P. copri 27 kDa (Pc-p27) stimulated T and B lymphocytes in 40% of patients with rheumatoid arthritis, but not in the control group or in patients with other rheumatic diseases [8,144,145]. This peptide is also presented by an HLA-DR receptor, which is consistent with existing data on HLA-DR and its relationship to the phenomenon of molecular mimicry.…”
Section: Molecular Mimicrysupporting
confidence: 75%
“…Rheumatoid arthritis (RA) is a systemic inflammatory disease whose pathogenesis is often characterized by the infiltration of proinflammatory synovial fibroblasts, elevated frequency of synovial osteoclasts, and progressive joint destruction (Smolen et al, 2016;Zhao et al, 2022). Multiple strategies to inhibit the proliferation of synovial fibroblasts and reinstate synovial homeostasis in RA could provide promising therapeutic directions (Chen et al, 2022b;Ji et al, 2022;Sandhu and Thelma, 2022). Recent studies have reported that the increased risk of RA disease might be associated with the dysfunction of the antioxidant system in fibroblast-like synoviocytes (FLS).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…RA mainly affects synovial joints, with inflammation of the synovial membrane (synovitis) characterized by angiogenesis, hyperplasia of the lining layer, and immune cell infiltration that stimulates local inflammation and, if untreated, can result in joint destruction and disability ( Rivellese and Pitzalis, 2021 ). Progress in therapeutic approaches and understanding of RA pathogenesis have improved patient prognosis and likely remission, while partial/non-response to conventional and biologic therapies in certain patients underlines the need for new therapeutics ( Sandhu and Thelma, 2022 ). Fibroblast-like synoviocytes (FLS) in the synovial lining develop aggressive phenotypes and are a main focus within the RA field, and the proportion of the surface marker CD90 correlates positively with the proportion of synovitis and synovial hypertrophy ( Wu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%